Uncovering the Truth Through Post-mortem: A Normative Analysis of Murder Victim Autopsies - Juswanto Ade Setiawan; Hasbuddin Khalid; Muhammad Azham Ilham (HORIZON PUBLIC LEGAL STUDIES, 2025)
This research aims to analyze the legal procedures for conducting post-mortems on murder victims in Indonesia and to determine the implications of post-mortems on human rights, particularly the rights of victims and their families, during the investigation of murder crimes. The research, entitled "Normative Analysis of Post-mortems on Murder Victims," utilizes a normative legal research method. This method emphasizes the analysis of statutory regulations, legal doctrine, and various related legal literature. Forensic autopsies play a crucial role in the criminal law evidentiary system, particularly in murder cases. They serve as a tool to determine the legitimate and objective cause of death and contribute significantly to the development of post mortem examinations (visum et repertum) as legally recognized evidence. Normatively, the procedure for post-mortem examinations has a clear legal basis, regulated by the Criminal Procedure Code (KUHAP), the Health Law, and other relevant regulations. Autopsies may be performed without the family's consent for law enforcement purposes, but must still be conducted with respect for human rights, cultural values, and professional ethics.